2009
DOI: 10.1002/hep.22730
|View full text |Cite
|
Sign up to set email alerts
|

Multiple division cycles and long-term survival of hepatocytes are distinctly regulated by extracellular signal-regulated kinases ERK1 and ERK2

Abstract: We investigated the specific role of the mitogen-activated protein kinase (MAPK) extracellular signal-regulated kinase 1 (ERK1)/ERK2 pathway in the regulation of multiple cell cycles and long-term survival of normal hepatocytes. An early and sustained epidermal growth factor (EGF)-dependent MAPK activation greatly improved the potential of cell proliferation. In this condition, almost 100% of the hepatocytes proliferated, and targeting ERK1 or ERK2 via RNA interference revealed the specific involvement of ERK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
8
44
0
Order By: Relevance
“…Recent studies have defined the functional significance of calcium signaling for efficient hepatocyte cell cycle progression from G 0 to G 1 and S phases in regenerating livers (15,38,52). Among the many intracellular mitogenic targets of calcium signaling, p44/42 ERK MAPKs are well-known mediators of hepatocyte cell cycle progression at the G 1 phase and S phase entry (9,24,57,65). In this study, we provide evidence that both ERK MAPK activation in response to 70% PH in vivo and ATP-treatment of isolated hepatocytes in vitro were dependent on intact P2Y2 purinergic receptor expression in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have defined the functional significance of calcium signaling for efficient hepatocyte cell cycle progression from G 0 to G 1 and S phases in regenerating livers (15,38,52). Among the many intracellular mitogenic targets of calcium signaling, p44/42 ERK MAPKs are well-known mediators of hepatocyte cell cycle progression at the G 1 phase and S phase entry (9,24,57,65). In this study, we provide evidence that both ERK MAPK activation in response to 70% PH in vivo and ATP-treatment of isolated hepatocytes in vitro were dependent on intact P2Y2 purinergic receptor expression in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to such a redundant function of both ERK isoforms, there are recent studies that have identified some isoform specific functions. Thus, ERK1 and ERK2 have been demonstrated to fulfil different roles in Ras-dependent signalling (Vantaggiato et al, 2006) and long-term survival of hepatocytes (Frémin et al, 2009). While some differences in ERK isoform signalling have been attributed to differences in the N-terminal domain of both isoforms (Marchi et al, 2008), other studies have shown that differences might be due to the expression level of each isoform (Lefloch et al, 2008;Lefloch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these studies, we found that further upregulation of the expression of cyclin B1 and CDK1 could result from Smad4 deficiency in HepG2 cells, whereas inhibition of the MEK/ERK signaling pathway efficiently attenuates BMP4-induced upregulation and maintained basal levels of cyclin B1 and CDK1 in HepG2 cells. MEK/ERK signaling is believed to play an important role in the regulation of cell proliferation and its signaling pathway is activated by different growth factors, including BMP4 cytokines (41,42). Growth factor-induced MEK/ ERK cascade is considered to be an inducer for the regulation of multiple phosphorylating proteins and their target proteins and to promote the interaction between retinoblastoma (Rb) protein and E2F-1 and to affect transcriptional regulation of target genes involved in cell-cycle control (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%